Biodegradation Potential of Cyanide and Nitrile using Bacteria of The Genus Rhodococcus - Afianisa, Salma; Saepudin, Endang; Sunarko, Bambang; Sulistinah, Nunik (Syntax Literate, 2024)
Cyanides and nitriles, characterized by their R-CN chains, are known for their toxicity, mutagenicity, and carcinogenicity, posing significant threats to environmental and human health. This study aims to explore the biodegradation capabilities of Rhodococcus sp. in breaking down cyanide and nitrile bonds. Rhodococcus pyridinivorans strain I-benzo was isolated from tanning waste and cultured in mineral media with a 20 mM benzonitrile substrate. The activity of this strain was tested using substrates such as benzonitrile, acetonitrile, acrylonitrile, benzamide, acetamide, and acrylamide, revealing positive reactions of nitrile hydratase and amidase enzymes through the Nessler measurement method, which indicated the production of ammonia and carboxylic acids. Furthermore, the degradation tests showed that the Vmax values for the biodegradation of potassium cyanide and sodium cyanide were 0.56 ppm/minute and 0.21 ppm/minute, respectively. These findings highlight the potential application of Rhodococcus pyridinivorans strain I-benzo in mitigating the environmental impact of cyanide and nitrile pollutants through efficient biodegradation.